High-toughness corrosion-resistant aluminum alloy and preparation method thereof
By optimizing the components and processes of the 5xxx aluminum alloy, an aluminum alloy containing T-Mg32(Al, Zn)49 phase and Al3(Sc, Zr) phase was prepared, which solved the problem of insufficient comprehensive performance of existing aluminum alloys in laser powder bed melting technology, and achieved improvements in high strength, high elongation and corrosion resistance, reducing the preparation cost and process complexity.
Patent Information
- Application Number
- CN202411922294.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
AI Technical Summary
The comprehensive performance of existing aluminum alloys in laser powder bed melting technology is insufficient, which cannot meet the performance requirements of modern manufacturing for high-strength, tough, corrosion-resistant aluminum alloys, and has high production costs and complex processes.
By optimizing the components of the 5xxx aluminum alloy and developing matching 3D printing and heat treatment processes, an aluminum alloy containing T-Mg32(Al, Zn)49 phase and Al3(Sc, Zr) phase was prepared. Combined with in-situ alloying powder making process and laser powder bed melting technology, high strength, high elongation and corrosion resistance were achieved.
The high strength, corrosion resistance and elongation of aluminum alloys have been significantly improved, with tensile strength reaching 514MPa-557MPa, with an elongation of more than 5.7-6.8%. The corrosion current is reduced and the pitting potential is increased, reducing the development cost and process complexity of the new alloy.
Smart Images

Figure CN119640105A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aluminum alloy additive manufacturing, and specifically relates to a high-strength and corrosion-resistant aluminum alloy and a preparation method thereof. Background Art
[0002] At present, additive manufacturing is one of the focuses of material preparation technology research. Among the many additive manufacturing technologies, laser powder bed fusion technology has attracted much attention because it does not require the use of molds and can achieve direct near-net forming of parts. Aluminum alloys have the advantages of low density, electrical and thermal conductivity, good plastic formability, good corrosion resistance, and high specific strength. A lot of research has been carried out in the field of laser powder bed fusion technology, and they are widely used in many fields such as transportation, shipbuilding, machinery manufacturing, and aerospace. Existing commercial aluminum alloys are often developed for specific industrial classifications, and their performance distribution is single. Although they perform well in individual fields, their comprehensive performance is often insufficient and cannot meet the performance requirements of modern manufacturing for high-strength, toughness, and corrosion-resistant aluminum alloys. Currently, commonly used aluminum alloys include 5xxx aluminum alloys and 7xxx aluminum alloys. The strength of 7xxx aluminum alloys is higher, but the corrosion resistance is poor. In contrast, 5xxx aluminum alloys are non-heat-treatable alloys, and they mainly rely on solid solution strengthening of Mg elements to improve mechanical properties. Although their corrosion resistance is superior, their mechanical properties are still significantly lower than those of aging-strengthening 7xxx alloys. At the same time, the alloy powders required for laser additive manufacturing often have high requirements on powder particle size distribution. Currently, most manufacturers use pre-alloying to prepare alloy powders for laser additive manufacturing. The powder making efficiency is low and the cost is high, which greatly limits the development of new aluminum alloys.
[0003] Patent document with publication number CN113817937A discloses a method for manufacturing 5xxx aluminum alloys, which can produce 5xxx aluminum alloy plates with a tensile strength of 215 MPa by rationally optimizing the content ratio of Fe element in the aluminum alloy. Although the 5xxx aluminum alloy produced by this preparation method has excellent corrosion resistance, its tensile strength and elongation are poor, which restricts the application of 5xxx aluminum alloys. Summary of the invention
[0004] The main purpose of the present invention is to overcome the deficiencies in the prior art, and the present invention provides a high-toughness, corrosion-resistant aluminum alloy and a preparation method thereof. The aluminum alloy designed by the present invention has the characteristics of high strength and corrosion resistance, and the development cost is low, and the preparation method is simple, short in cycle, and high in flexibility.
[0005] The present invention is based on 5xxx series aluminum alloy, optimizes the components, and develops a 3D printing process and a corresponding heat treatment process that match the 5xxx series aluminum alloy, thereby obtaining a high-quality aluminum alloy that is corrosion-resistant, high-strength, and high-elongation.
[0006] The invention discloses a high-strength, tough and corrosion-resistant aluminum alloy, which consists of the following components in percentage by mass: 3.5-4.6 wt.% of Mg, 1.3-1.5 wt.% of Zn, 0.1-0.4 wt.% of Sc, 0.4-0.5 wt.% of Zr, 0.4-0.5 wt.% of Cu, and the remainder of Al.
[0007] The invention discloses a high-strength and tough corrosion-resistant aluminum alloy, which consists of the following components in mass percentage: Mg: 4.1-4.4 wt.%, Zn: 1.4-1.45 wt.%, Sc: 0.28-0.32 wt.%, Zr: 0.45-0.5 wt.%, Cu: 0.4-0.45 wt.%, and the rest is Al.
[0008] The invention discloses a high-strength, tough and corrosion-resistant aluminum alloy, which consists of the following components in mass percentage: Mg: 4.2-4.22 wt.%, Zn: 1.45-1.47 wt.%, Sc: 0.29-0.31 wt.%, Zr: 0.47-0.49 wt.%, Cu: 0.4-0.42 wt.%, and the rest is Al.
[0009] The invention discloses a high-strength and corrosion-resistant aluminum alloy containing T-Mg 32 (Al, Zn) 49 Mutually.
[0010] As a preferred embodiment, the present invention provides a high-toughness corrosion-resistant aluminum alloy, which contains T-Mg 32 (Al, Zn) 49 Phase and Al 3 (Sc, Zr) phase.
[0011] In the present invention, T-Mg 32 (Al, Zn) 49 The phase is a body-centered cubic lattice with a lattice constant of 1.416 nm. Each unit cell contains 162 atoms, and its main components are Al, Mg and Zn. 32 (Al, Zn) 49 The phase exhibits excellent thermal stability and precipitation strengthening, and its strengthening effect is better than that of β-Al 3 Mg 2 The phase is more excellent. And T-Mg 32 (Al, Zn) 49 The potential difference between the phase and the matrix is lower than that of the strengthening phase (η-Mg 2 Zn phase) and the substrate, so the alloy has a smaller tendency to corrode than 7xxx series aluminum alloys. 32 (Al, Zn) 49 The precipitation of β-Al3 Mg 2 The formation of precipitation phase, thereby changing the corrosion mode of the alloy, effectively improving the mechanical properties and corrosion resistance of aluminum alloy. Now on this basis, appropriate amounts of alloying elements such as Sc and Zr are added to form Al 3 (Sc, Zr) composite particles act as nucleating agents to refine grains and improve hot cracking and formability. 32 (Al, Zn) 49 Phase and Al 3 The synergistic effect of the (Sc, Zr) phases, as well as the strengthening mechanisms such as the precipitation of multiple stable second phases and grain refinement make the fine precipitates dispersed within the crystal and the precipitates discontinuously distributed at the grain boundaries, achieving a high degree of coordination between dislocation strengthening and precipitation strengthening, and improving the strength and thermal stability of the alloy.
[0012] The invention discloses a method for preparing a high-strength and corrosion-resistant aluminum alloy, comprising the following steps: using aluminum alloy powder as a printing raw material, adopting laser powder bed melting technology to print to obtain a printed product; during printing, controlling: The laser power is 250 W-350 W, the laser scanning speed is 800 mm / s-1200 mm / s, the laser spot diameter is 60 μm-80 μm, the scanning interval is 0.02 mm-0.05 mm, the powder thickness is 0.03 mm-0.05 mm, and the substrate temperature is 120℃-140℃; The raw material powder consists of the following components in mass percentage: Mg 3.5-4.6 wt.%, Zn 1.3-1.5 wt.%, Sc 0.1-0.4 wt.%, Zr 0.4-0.5 wt.%, Cu 0.4-0.5 wt.%, and the rest is Al.
[0013] When used in industry, 60-80% by mass of 5024 aluminum alloy powder (5xxx series aluminum alloy powder that can be formed by LPBF and has been commercialized) and 20-40% by mass of 7050 aluminum alloy powder (7xxx series aluminum alloy powder that cannot be formed by LPBF and has been commercialized) are mixed evenly to obtain the raw material powder used for printing.
[0014] When used in industry, accurately weigh the metal powders of raw materials 5024 and 7075 (the above two powders are currently commercialized and there is no need to atomize and powder them yourself); then, use the in-situ alloying method to mechanically mix the raw metal powders for 10 h-15 h to obtain 5xxx / 7xxx series cross-linked aluminum alloy powders for laser additive manufacturing, and package the 5xxx / 7xxx series cross-linked aluminum alloy powders in a vacuum bag for later use.
[0015] Furthermore, the microscopic unit cell structure of the raw metal powder is a face-centered cubic crystal structure (FCC phase). Using the aluminum alloy raw metal powder in the FCC phase is conducive to obtaining a high-strength and corrosion-resistant printed product.
[0016] The raw material used in the present invention has high sphericity, and the number of symbiotic satellite spherical powders is small. The particle size of the powder is 15 μm-35 μm. The use of alloy powders in the above particle size range is beneficial to the fluidity and formability of the raw material powder in the subsequent laser powder bed melting process.
[0017] Furthermore, the laser powder bed fusion technology additive manufacturing includes the following steps: S1. Draw the three-dimensional graphics of the required parts through software; S2. Select raw material powder with a particle size of 15 μm-35 μm and dry it in a vacuum drying oven to remove air and water. The vacuum drying temperature is 90 ℃-110 ℃ and the vacuum drying time is 4 h-6 h. S3. The vacuum-dried raw powder is placed in the powder supply cylinder of the LPBF printer, the printer is turned on, and the 3D printing operation is started. The process parameters of 3D printing are: laser power of 250 W-350 W, laser scanning speed of 800 mm / s-1200 mm / s, laser spot diameter of 60 μm-80 μm, scanning spacing of 0.02 mm-0.05 mm, powder thickness of 0.03 mm-0.05 mm, and substrate temperature of 120 ℃-140 ℃; the raw powder is scanned and sintered layer by layer. When the laser scanning completes a layer, the printing work plane is lowered, and the next layer of raw powder is laid on its top surface, and then a new layer is laser scanned, and this is repeated to obtain a 3D printed sample; the process parameters of the above-mentioned laser powder bed fusion technology can be used to prepare aluminum alloy parts with excellent mechanical properties and corrosion resistance; S4. Separate the formed part from the substrate by wire cutting, clean the residual powder, and obtain aluminum alloy parts.
[0018] Furthermore, in step S3, the relative rotation angle between adjacent layers during 3D printing is 0°, 45°, 67° or 90°; the scanning strategy of 3D printing is chessboard scanning or line scanning or a combination of the two, the chessboard scanning chessboard is square or rectangular, and the chessboard area is 4 mm 2 -25 mm 2 .
[0019] The printed product obtained by the present invention has more excellent mechanical properties and corrosion resistance, with a tensile strength of 514MPa-557MPa, an elongation of more than 5.7-6.8%, and a corrosion current of 7.8×10 -10 -8.4×10 -10mA / cm 2 , the pitting potential is -0.506 V--0.402 V.
[0020] The alloy designed by the present invention can be prepared by laser powder bed fusion additive manufacturing, powder metallurgy, injection molding, hot isostatic pressing or welding repair and other processes.
[0021] Furthermore, the printed product is heat treated, and the heat treatment process is as follows: first, the 3D printed sample is aged at a temperature of 400-450 °C, a heating rate of 5-10 °C / min, and a holding time of 3-6 h. Vacuum or argon protection is used during the aging treatment. After the aging treatment, water quenching is performed at a water temperature of 20-30 °C and a transfer time of no more than 10 s. After water quenching, re-aging treatment is performed at a re-aging temperature of 110-130 °C and a holding time of 20-25 h. After the re-aging treatment, the sample is air-cooled to room temperature.
[0022] Furthermore, the microscopic grain size of the aluminum alloy parts prepared after heat treatment is 0.2 μm-2 μm. The small grain size can play a role in fine grain strengthening, further improving the mechanical properties of the aluminum alloy parts; the metallographic phase of the aluminum alloy parts prepared after heat treatment includes a main phase and a reinforcement phase, the main phase is an α-Al matrix phase, and the reinforcement phase is a T-Mg 32 (Al, Zn) 49 Phase and Al 3 (Sc, Zr) phase. T-Mg 32 (Al, Zn) 49 Phase and Al 3 The (Sc, Zr) phase is dispersed in the main phase α-Al matrix phase, playing the role of grain refinement and precipitation strengthening. 32 (Al, Zn) 49 The precipitation of β-Al 3 Mg 2 The formation of precipitation phase changes the corrosion mode of the alloy and effectively improves the mechanical properties and corrosion resistance of the aluminum alloy.
[0023] Furthermore, the density of the 3D printed sample obtained in step S3 is above 99.5%, the tensile strength is 410MPa-430MPa, the yield strength is 360MPa-380MPa, and the elongation is 10.5%-12.3%; The tensile strength of the aluminum alloy parts produced after heat treatment is 514 MPa-557 MPa, the yield strength is 480 MPa-508 MPa, and the elongation is 5.7%-6.8%; the tensile strength of the aluminum alloy parts at 200°C is 240 MPa-260 MPa, and the yield strength is 220 MPa-230 MPa.
[0024] In summary, the present invention has at least one of the following beneficial effects: 1. The present invention obtains a novel 5xxx / 7xxx series cross-linked aluminum alloy powder by in-situ mixing commercial 5xxx series laser additive manufacturing aluminum alloy powder with 7xxx series aluminum alloy powder that is not suitable for laser additive manufacturing, so as to enhance the comprehensive performance of the alloy and reduce the preparation cost of the new alloy.
[0025] 2. The new 5xxx / 7xxx cross-linked aluminum alloy powder for laser additive manufacturing provided by the present invention is prepared by in-situ alloying of 5024 aluminum alloy powder and 7075 aluminum alloy powder to obtain AlMgZnCuScZr cross-linked alloy powder, and introduces the main alloying element Zn of the 7xxx series into the 5xxx series alloy, so that the alloy maintains high corrosion resistance while greatly improving its mechanical properties. The prepared aluminum alloy includes the main phase FCC phase and the reinforcing phase T-Mg 32 (Al, Zn) 49 Phase and Al 3 (Sc, Zr) phase, fine grains, and the comprehensive effects of solid solution strengthening, precipitation phase strengthening and fine grain strengthening are achieved at the same time. Therefore, it has excellent mechanical properties and corrosion resistance. The tensile strength of aluminum alloy reaches 523 MPa, the yield strength reaches 497 MPa, the elongation is above 6.4%, and the corrosion current reaches 8.2×10 -10 mA / cm 2 , the pitting potential reaches -0.506 V.
[0026] 3. The new aluminum alloy powder for laser additive manufacturing provided by the present invention is designed according to the composition ratio of 5024 alloy powder and 7075 alloy powder, and the synergistic effect between the alloy elements is used to form a uniformly distributed T-Mg 32 (Al, Zn) 49 and Al 3 The (Sc, Zr) phase disperses the fine precipitates in the crystal and inhibits the β-Al 3 Mg 2 The formation of precipitation phase further improves the mechanical properties and corrosion resistance of aluminum alloy.
[0027] 4. The present invention combines the in-situ alloying powder making process and the laser powder bed melting technology, and uses 5024 alloy powder and 7075 alloy powder in a designed proportion according to the composition for laser powder bed melting forming. The new alloy has a low development cost, a simple preparation process, a short cycle, high flexibility, and can improve the mechanical properties and corrosion resistance of 5xxx series aluminum alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 This is a SEM-EDS image of the 5xxx / 7xxx series cross-linked aluminum alloy powder prepared in Example 1; Figure 2 XRD diagram of 5xxx / 7xxx series cross-linked aluminum alloy; Figure 3 TEM image of the aluminum alloy prepared in Example 1; Figure 4 This is the Vickers hardness diagram of 5xxx / 7xxx series cross aluminum alloys; Figure 5 is a polarization curve diagram of the aluminum alloy prepared in Example 1; Figure 6 TEM image of the aluminum alloy prepared in Example 2; Figure 7 is a polarization curve diagram of the aluminum alloy prepared in Example 2; Figure 8 This is a SEM image of the aluminum alloy prepared in Example 3; Fig. 9 is a polarization curve diagram of the aluminum alloy prepared in Example 3; Fig.10 This is a polarization curve diagram of the aluminum alloy prepared in Comparative Example 2; Fig.11 This is a metallographic picture of the aluminum alloy prepared in Comparative Example 5. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0031] Example 1 The preparation method of 5xxx / 7xxx series cross aluminum alloy powder for laser additive manufacturing comprises the following steps: first, according to the composition design of 5xxx / 7xxx series cross aluminum alloy for laser additive manufacturing, the raw material 5024 and 7050 aluminum metal powders are accurately weighed, the weight of 5024 aluminum alloy powder in this embodiment 1 is 800 g, the weight of 7050 aluminum alloy powder is 200 g, and the chemical composition and mass percentage thereof are: Mg: 4.21 wt.%, Zn: 1.46 wt.%, Sc: 0.30 wt.%, Zr: 0.48 wt.%, Cu: 0.41 wt.%, and the rest is Al; then, the raw material metal powders are mechanically mixed for 15 h by an in-situ alloying method to obtain 5xxx / 7xxx series cross aluminum alloy powder for laser additive manufacturing, wherein the particles are spherical powders and the particle size of the powder is 15 μm-35 μm.
[0032] The 5xxx / 7xxx series cross-linked aluminum alloy powder for laser additive manufacturing as described above is used for laser powder bed melting additive manufacturing, powder metallurgy, injection molding, hot isostatic pressing or welding repair; wherein the laser powder bed melting additive manufacturing includes the following steps: S1. Draw the three-dimensional graphics of the required parts through software: S2. Select 5xxx / 7xxx cross aluminum alloy powder with a particle size of 15 μm-35 μm and dry it in a vacuum drying oven to remove air and water. The vacuum drying temperature is 110 °C and the vacuum drying time is 5 h. S3. The aluminum alloy powder after vacuum drying was put into the powder supply cylinder of the LPBF printer, and the LPBF printer was turned on to start the 3D printing operation. The process parameters of 3D printing were as follows: laser power of 350 W, laser scanning speed of 1000 mm / s, laser spot diameter of 70 μm, scanning spacing of 0.03 mm, powder thickness of 0.03 mm, substrate temperature of 140 °C, and the 5xxx / 7xxx series cross aluminum alloy powder was scanned and sintered layer by layer. After the laser scanning completed a layer, the printing work plane was lowered, and the next layer of 5xxx / 7xxx series cross aluminum alloy powder was laid on its top surface, and then the laser scanned a new layer. During the 3D printing process, the relative rotation angle between adjacent layers was 67°; the scanning strategy of 3D printing was a line scanning strategy, and the scanning method was a 67° rotation between adjacent layers, which was repeated to obtain a 3D printed sample; S4. Separate the formed part from the substrate by wire cutting, clean the residual powder, and obtain aluminum alloy parts (density is 99.6%).
[0033] Figure 1 This is the SEM-EDS image of the new 5xxx / 7xxx series cross-linked aluminum alloy powder prepared in Example 1. Figure 1The distribution of different elements in the aluminum alloy powder can be observed.
[0034] Figure 2 The XRD pattern of the aluminum alloy prepared in Example 1 is shown in FIG. Figure 2 It can be seen that the aluminum alloy powder is a single FCC phase. In addition to the matrix phase α-Al phase, a small amount of reinforcement phase T-Mg is detected in the aluminum alloy parts. 32 (Al, Zn) 49 Phase and Al 3 (Sc, Zr) phase.
[0035] Figure 3 This is the TEM image of the aluminum alloy component prepared in Example 1. Figure 3 It can be seen that the grains of the prepared aluminum alloy parts are small and uniform, the grain size is mainly distributed in the range of 0.8 μm-1.4 μm, and the average grain size is 1.05 μm.
[0036] Table 1 shows the tensile curve performance results of the prepared aluminum alloy parts. It can be seen from Table 1 that the tensile strength of the aluminum alloy parts reaches 423 MPa, the yield strength reaches 375 MPa, and the elongation reaches 11.6%.
[0037] Figure 4 The Vickers hardness diagram of the aluminum alloy prepared in Example 1 is shown in FIG. Figure 4 It can be seen that the Vickers hardness of the aluminum alloy parts prepared in Example 1 reaches 107 Hv.
[0038] Figure 5 This is the polarization curve of the aluminum alloy component prepared in Example 1. Figure 5 It can be seen that the corrosion current reaches 4.47×10 -8 A, the pitting potential reaches -0.621 V, and the corrosion potential reaches 0.735 V.
[0039] Example 2 The composition, proportion and preparation method of the new aluminum alloy powder for laser additive manufacturing in this embodiment 2 are the same as those in embodiment 1. The steps of using the new aluminum alloy powder for laser additive manufacturing in laser powder bed melting additive manufacturing are the same as those in embodiment 1, except that the aluminum alloy parts prepared in step S4 are subjected to aging heat treatment. The heat treatment process is: Firstly, the 3D printed samples were aged at 325 °C, with a heating rate of 5 °C / min and a holding time of 4 h. Argon protection was used during the aging treatment. After aging treatment, water quenching was performed, the water temperature was 25 °C, and the transfer time was 10 s; After water quenching, the steel was re-aged at 120 °C for 24 h, and then air-cooled to room temperature.
[0040] from Figure 2 It can be seen that in addition to the matrix phase α-Al phase, the aluminum alloy prepared in Example 2 also has a reinforcing phase T-Mg 32 (Al, Zn) 49 Phase and Al 3 (Sc, Zr) phase, T-Mg in aluminum alloy after heat treatment 32 (Al, Zn) 49 The intensity of the phase characteristic peaks is enhanced, indicating that the heat treatment effectively promotes the T-Mg 32 (Al, Zn) 49 Phase separation.
[0041] Figure 4 The Vickers hardness diagram of the aluminum alloy prepared in Example 2 is shown in FIG. Figure 4 It can be seen that the Vickers hardness of Example 2 reaches 134 Hv.
[0042] Figure 6 TEM image and grain size distribution diagram of the aluminum alloy parts prepared in Example 2. Figure 6 It can be seen that the prepared aluminum alloy has fine and uniform grains, the grain size is mainly distributed in the range of 0.8 μm-1.4 μm, and the average grain size is 1.09 μm.
[0043] From the tensile curve performance results in Table 1, it can be seen that the tensile strength of the aluminum alloy reaches 523 MPa, the yield strength reaches 497 MPa, and the elongation reaches 6.4%.
[0044] Figure 7 This is the polarization curve of the aluminum alloy component prepared in Example 2. Figure 7 It can be seen that the corrosion current reaches 8.20×10 -10 A, pitting potential reaches -0.506 V, and corrosion potential reaches -0.668 V. Compared with Example 1, the corrosion current of Example 2 is reduced, the pitting potential is increased, and the corrosion potential is reduced, indicating that after heat treatment, T-Mg 32 (Al, Zn) 49 The precipitation of the phase improves the corrosion resistance of the sample, increases the pitting resistance, and significantly improves the corrosion performance. This is because the addition of the Zn element modifies the alloy passivation film, thereby changing the corrosion mode of the alloy in Example 2 and improving the corrosion resistance of the alloy.
[0045] In this embodiment 2, aging heat treatment was performed on the basis of embodiment 1. Figure 3 and Figure 8It can be seen that new T-Mg is precipitated. 32 (Al, Zn) 49 Phase, further enhancing the comprehensive mechanical properties of aluminum alloy parts. Through testing, the density of the sample formed by laser powder bed melting of the powder fine powder (15 μm-35 μm) of Example 2 is 99.6%, the tensile strength of the printed sample reaches 523 MPa, the yield strength reaches 497 MPa, and the elongation reaches 6.4%; the tensile strength of the material at 200°C reaches 244 MPa, the yield strength reaches 226 MPa, and the elongation reaches 27%.
[0046] Example 3 In this Example 3, the weight of the 5024 aluminum alloy powder is 600 g, the weight of the 7050 aluminum alloy powder is 400 g, and the chemical composition and mass percentage thereof are: Mg: 3.66 wt.%, Zn: 2.44 wt.%, Sc: 0.78 wt.%, Zr: 0.38 wt.%, Cu: 0.85 wt.%, and the rest is Al; the powder preparation method in Example 3 is the same as that in Example 1, and the steps of using the new aluminum alloy powder for laser additive manufacturing for laser powder bed melting additive manufacturing are the same as those in Example 1, and the only difference is the composition and ratio of the aluminum alloy powder.
[0047] from Figure 2 It can be seen that in addition to the matrix phase α-Al phase, a large amount of strengthening phase T-Mg 32 (Al, Zn) 49 Phase, compared with Example 1, it is found that the diffraction peak intensity of the enhanced phase is significantly increased, indicating that the change in the ratio promotes the formation of the primary precipitated phase.
[0048] Figure 4 The Vickers hardness diagram of the aluminum alloy prepared in Example 3 is shown in FIG. Figure 4 It can be seen that the Vickers hardness of Example 3 reaches 103 Hv.
[0049] Figure 8 This is the SEM-EDS image of the aluminum alloy parts prepared in Example 3. Figure 3 It can be seen that the precipitated phases rich in Mg and Zn elements in the prepared aluminum alloy parts continuously precipitate along the grain boundaries to form a network, which reduces the intergranular corrosion resistance of the alloy.
[0050] From the tensile curve performance results in Table 1, it can be seen that the tensile strength of the aluminum alloy parts reaches 407 MPa, the yield strength reaches 376 MPa, and the elongation reaches 8.7%. Due to the presence of the network precipitation phase, the cracks preferentially initiate and extend along the grain boundaries, resulting in a decrease in mechanical properties and elongation.
[0051] Fig. 9 This is the polarization curve of the aluminum alloy component prepared in Example 3. Figure 6 It can be seen that the corrosion current reaches 5.88×10 -8 A, the pitting potential reaches -0.632 V, and the corrosion potential reaches -0.724 V. Compared with Example 1, the continuity of the precipitated phase in Example 3 is enhanced, resulting in an increase in the degree of intergranular corrosion and an increase in the pitting depth.
[0052] Comparative Example 1 Comparative Example 1 provides a laser powder bed melting forming method for a 5xxx series aluminum alloy sample, comprising the following steps: 5024 alloy powder (commercially available, with a purity of 99.9% and a particle size of 15 μm-35 μm) is subjected to laser powder bed melting to prepare a 5xxx series aluminum alloy. The specific steps are: placing the raw material powder in the feed bin of the LPBF printer, and using the laser to heat the 2 Laser; the laser spot is set to 70 μm, the scanning interval is set to 0.03 mm, the laser power is set to 350 W, and the laser scanning speed is set to 800 mm / s. The raw material powder is scanned and sintered layer by layer. After each laser scanning completes a layer, the printing work plane is lowered, and the next layer of raw material powder is laid on its top surface, and then the laser scans a new layer. Repeat the above process and finally prepare the 5xxx series aluminum alloy sample.
[0053] pass Figure 2 It can be found that the 5xxx aluminum alloy prepared in Comparative Example 1 is subjected to phase analysis by XRD, and it is found that the matrix phase of the 5xxx aluminum alloy prepared in Comparative Example 1 is an α-Al phase, and also includes a small amount of reinforcing phase Al 3 (Sc, Zr) phase, no T-Mg 32 (Al, Zn) 49 Phase diffraction peak.
[0054] Figure 4 The Vickers hardness diagram of the aluminum alloy prepared in Comparative Example 1 is shown in FIG. Figure 4 It can be seen that the Vickers hardness of Comparative Example 1 reaches 91 Hv.
[0055] Comparative Example 2 The difference between Comparative Example 2 and Comparative Example 1 is that in Comparative Example 2, the aluminum alloy is subjected to aging heat treatment, aging treatment is performed at 325°C for 4 hours, and then re-aging treatment is performed at 120°C for 24 hours.
[0056] Figure 4 The Vickers hardness diagram of the aluminum alloy prepared in Comparative Example 2 is shown in FIG. Figure 4 It can be seen that the Vickers hardness of Comparative Example 2 reaches 122 Hv.
[0057] Fig.10 The polarization curve of the 5xxx aluminum alloy prepared in Comparative Example 2 is shown in FIG. Fig.10 It can be seen that the corrosion current reaches 3.71×10 -8 A, pitting potential reaches -0.611 V, and corrosion potential reaches -0.749 V. Compared with Example 2, the corrosion current of Comparative Example 2 is increased, and the pitting potential is lower. The difference between the pitting potential and the corrosion potential of the alloy in Comparative Example 2 is lower than that in Example 2, indicating that the pitting resistance is smaller, so pitting is more likely to occur, indicating that the corrosion resistance of the cross alloy in Example 2 is better than that of the 5xxx series aluminum alloy in Comparative Example 2.
[0058] The tensile strength of the aluminum alloy of Comparative Example 2 was tested by the same tensile test as in Example 2. The heat treatment process parameters of the 5xxx series aluminum alloy sample in Comparative Example 2 were the same as those in Example 2. As can be seen from Table 1, after heat treatment, the tensile strength of the aluminum alloy prepared in Comparative Example 2 reached 430 MPa, the yield strength reached 411 MPa, and the elongation was 10.3%. Compared with Example 2, the mechanical properties of Comparative Example 2 are significantly lower than those of the aluminum alloy prepared in Example 2.
[0059] Comparative Example 3 This comparative example 3 relates to the material prepared in Example 1 in the patent application document “Method for preparing Al-Mg-based high-strength aluminum alloy by selective laser melting” (application number: 202110188824.6).
[0060] In this comparative example 3, Al-4.6Mg-0.66Sc-0.42Zr-0.49Mn pre-alloyed powder prepared by argon atomization method is selected. The powder is spherical or nearly spherical, and the powder particle size distribution range is 22 μm-55 μm.
[0061] According to the shape and size of the required formed parts, the corresponding CAD model was designed by computer, and the model was sliced into equal thickness in the height direction, with a thickness of 30 μm. A Z-shaped scanning path was used, and the path of each layer was scanned by rotating 67° clockwise. The slices and scanning paths were saved as STL files and input into the laser powder bed melting equipment. The molding parameters were set as follows: laser power 200 W, scanning rate 700 mm / s, scanning spacing 135 μm, and powder thickness 30 μm. The parts prepared by laser powder bed melting technology were placed in a vacuum furnace, heated to 350 ℃, kept warm for 8 h, and water-cooled.
[0062] The density of the A1-4.6Mg-0.66Sc-0.42Zr-0.49Mn alloy prepared by laser powder bed fusion technology reaches 99.5%, with a small amount of pores and no cracks. The alloy structure is composed of equiaxed crystals and columnar crystals. The grain size of some equiaxed crystals is small, reaching less than 100 nm.
[0063] Al in the microstructure of A1-4.6Mg-0.66Sc-0.42Zr-0.49Mn alloy prepared by laser powder bed fusion technology 3 The dispersed distribution of (Sc, Zr) particles can improve the mechanical properties of the A1-4.6Mg-0.66Sc-0.42Zr-0.49Mn alloy.
[0064] The mechanical properties of the parts were tested at room temperature, and the tensile strength reached 500 MPa, the yield strength reached 463 MPa, and the elongation reached 10.2%. Compared with Example 2, Comparative Example 3 uses the same forming process as Example 2, and the tensile strength and yield strength of the alloy in Comparative Example 3 are lower than the mechanical properties of the alloy in Example 2.
[0065] Compared with Example 1, the pre-alloyed powder preparation process used in Comparative Example 3 is expensive, has a long preparation cycle, and has poor comprehensive performance. The in-situ alloying powder preparation process used in Example 1 can reduce the preparation cost of the new alloy and quickly manufacture a new high-strength and corrosion-resistant aluminum alloy based on the existing mature commercial aluminum alloy system.
[0066] Comparative Example 4 Comparative Example 4 relates to the material prepared in Example 1 in the patent application document “A corrosion-resistant Al-Mg-Mn-Sc aluminum alloy and its preparation method” (application number: 202211159227.1).
[0067] This comparative example 4 proposes a corrosion-resistant Al-Mg-Mn-Sc aluminum alloy for preparing a corrosion-resistant aluminum alloy for light construction. Specifically, the aluminum alloy material comprises the following components by mass percentage: Mg: 5.5%, Mn: 0.7%, Sc: 0.15%, Zn: 0.4%, Zr: 0.02%, and the balance is Al. The mechanical properties of the parts were tested at room temperature, and the tensile strength reached 423 MPa, the yield strength reached 265 MPa, and the shear performance reached 211 MPa.
[0068] Compared with Example 2, the tensile strength and yield strength of the alloy in Comparative Example 4 are significantly lower than those in Example 2, indicating that the mechanical properties of the 5xxx / 7xxx series cross-linked aluminum alloy in Example 2 are greatly improved compared with the general corrosion-resistant 5xxx series aluminum alloy.
[0069] Comparative Example 5 In Comparative Example 5, the weight of the 5024 aluminum alloy powder is 200 g, the weight of the 7050 aluminum alloy powder is 800 g, and the chemical composition and mass percentage thereof are: Mg: 2.63 wt.%, Zn: 4.86 wt.%, Sc: 0.26 wt.%, Zr: 0.11 wt.%, Cu: 1.68 wt.%, and the rest is Al; the powder preparation method of Comparative Example 5 is the same as that of Example 1, and the steps of using the new aluminum alloy powder for laser additive manufacturing for laser powder bed melting additive manufacturing are the same as those in Example 1, and the only difference is the composition and ratio of the aluminum alloy powder.
[0070] Figure 4 The Vickers hardness diagram of the aluminum alloy prepared in Comparative Example 5 is shown in FIG. Figure 4 It can be seen that the Vickers hardness of Comparative Example 5 is only 72 Hv.
[0071] Fig.11 This is a metallographic picture of the aluminum alloy parts prepared in Comparative Example 5. Figure 1 It can be observed that due to the change in alloy ratio, the reduction in solidification range leads to a large number of hot cracks appearing along the longitudinal direction of the molten pool during the forming process, and the voids caused by overburning of elements increase significantly. The change in powder ratio in Comparative Example 5 leads to a significant increase in alloy defects and failure to form normally.
[0072]
[0073] As can be seen from the above table, Table 1 lists the tensile test results of the alloys prepared using the corresponding process conditions. The results show that the tensile strength and yield strength of the 5xxx / 7xxx series cross aluminum alloy materials prepared according to the alloy composition and preparation process of the present invention are greatly improved. 32 (Al, Zn) 49 Phase and Al 3 The synergistic effect of the (Sc, Zr) phase, as well as the strengthening mechanisms such as the precipitation of the multi-stable second phase and grain refinement make the fine precipitation phase dispersed in the crystal and the precipitation phase discontinuously distributed at the grain boundary, achieving a high degree of coordination between dislocation strengthening and precipitation strengthening, thereby improving the strength and thermal stability of the alloy. Therefore, it can be proved that the mechanical properties of the 5xxx / 7xxx cross aluminum alloy prepared by the present invention are significantly improved.
[0074]
[0075] Table 2 lists the electrochemical test results of the alloys prepared by Example 1, Example 2 and Comparative Example 2. The results show that the corrosion current of the 5xxx / 7xxx cross aluminum alloy material prepared by the present invention is reduced, the pitting potential is increased, and the corrosion potential is reduced. The difference between the pitting potential and the corrosion potential is used in electrochemistry to characterize the pitting resistance. The results show that the pitting resistance of the alloy in Example 2 is greatly increased, and the corrosion performance is significantly improved. This is because the addition of Zn element modifies the alloy passivation film, and the newly generated T-Mg 32 (Al, Zn) 49 Phase precipitation has an effect on β-Al 3 Mg 2 The formation of precipitated phase has an inhibitory effect, which in turn changes the corrosion mode of AlMgZnCuScZr alloy and improves the corrosion resistance of the alloy.
[0076] In summary, the present invention introduces the main alloying element Zn of the 7xxx series into the 5xxx series alloys through the design strategy of crossover alloying, and develops a new AlMgZnCuScZr alloy. The obtained alloy has significant improvements in mechanical properties and corrosion resistance.
[0077] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A high-strength, tough, corrosion-resistant aluminum alloy, characterized in that: The high-strength and tough corrosion-resistant aluminum alloy consists of the following components, measured in mass percentage: Mg 3.5-4.6 wt.%, Zn 1.3-1.5 wt.%, Sc 0.1-0.4 wt.%, Zr 0.4-0.5 wt.%, Cu 0.4-0.5 wt.%, and the remainder is Al.
2. The high-strength, toughness, corrosion-resistant aluminum alloy according to claim 1, characterized in that: In terms of mass percentage, it is composed of the following components: Mg: 4.1-4.4 wt.%, Zn: 1.4-1.45 wt.%, Sc: 0.28-0.32 wt.%, Zr: 0.45-0.5wt.%, Cu: 0.4-0.45 wt.%, and the rest is Al.
3. The high-toughness, corrosion-resistant aluminum alloy according to claim 1, characterized in that: It contains T-Mg 32 (Al, Zn) 49 Mutually.
4. The high-toughness, corrosion-resistant aluminum alloy according to claim 1, characterized in that: It contains T-Mg 32 (Al, Zn) 49 phase and Al3(Sc,Zr) phase.
5. A method for preparing a high-strength, tough, corrosion-resistant aluminum alloy, characterized in that: The method comprises the following steps: using aluminum alloy powder as printing material, adopting laser powder bed melting technology, and printing to obtain a printed product; and controlling during printing: The laser power is 250 W-350 W, the laser scanning speed is 800 mm / s-1200 mm / s, the laser spot diameter is 60 μm-80 μm, the scanning interval is 0.02 mm-0.05 mm, the powder thickness is 0.03 mm-0.05 mm, and the substrate temperature is 120 ℃-140 ℃; The raw material powder consists of the following components in mass percentage: Mg 3.5-4.6 wt.%, Zn 1.3-1.5 wt.%, Sc 0.1-0.4 wt.%, Zr 0.4-0.5 wt.%, Cu 0.4-0.5 wt.%, and the rest is Al.
6. The method for preparing a high-toughness, corrosion-resistant aluminum alloy according to claim 5, characterized in that: 60-80% by mass of 5024 aluminum alloy powder and 20-40% by mass of 7050 aluminum alloy powder are selected and mixed evenly to obtain raw material powder used for printing; the particle size of the powder used is 15 μm-35 μm.
7. The method for preparing a high-toughness, corrosion-resistant aluminum alloy according to claim 5, characterized in that: The laser powder bed fusion technology additive manufacturing includes the following steps: S1. Draw the three-dimensional graphics of the required parts through software; S2. Select raw material powder with a particle size of 15 μm-35 μm and dry it in a vacuum drying oven to remove air and water. The vacuum drying temperature is 90 ℃-110 ℃ and the vacuum drying time is 4 h-6 h. S3. The vacuum-dried raw material powder is placed in the powder supply cylinder of the laser powder bed fusion (LPBF) printer, the printer is turned on, and the 3D printing operation is started. The process parameters of 3D printing are: laser power of 250 W-350 W, laser scanning speed of 800 mm / s-1200 mm / s, laser spot diameter of 60 μm-80 μm, scanning spacing of 0.02 mm-0.05 mm, powder thickness of 0.03 mm-0.05 mm, and substrate temperature of 120 ℃-140 ℃; the raw material powder is scanned and sintered layer by layer. When the laser scanning completes one layer, the printing work plane is lowered, and the next layer of raw material powder is laid on its top surface, and then the laser scans a new layer, and this is repeated to obtain a 3D printed sample; S4. Separate the formed part from the substrate by wire cutting, clean the residual powder, and obtain aluminum alloy parts.
8. The method for preparing a high-strength, tough, corrosion-resistant aluminum alloy according to claim 5, characterized in that: In step S3, the relative rotation angle between adjacent layers during 3D printing is 0°, 45°, 67° or 90°; the scanning strategy for 3D printing is chessboard scanning or line scanning or a combination of the two, the chessboard scanning chessboard is square or rectangular, and the chessboard area is 4 mm 2 -25 mm 2 .
9. The method for preparing a high-toughness, corrosion-resistant aluminum alloy according to claim 5, characterized in that: The obtained printed product has a tensile strength of 514 MPa-557 MPa, an elongation of 5.7-6.8% and a corrosion current of 7.8×10 -10 mA / cm 2 -8.4×10 -10 mA / cm 2 , the pitting potential is -0.506 V--0.402 V.
10. The method for preparing a high-strength, tough, corrosion-resistant aluminum alloy according to claim 5, characterized in that: The printed product is heat treated, and the heat treatment process is as follows: first, the 3D printed sample is aged at a temperature of 400-450 °C, a heating rate of 5-10 °C / min, and a holding time of 3-6 h. Vacuum or argon protection is used during the aging treatment. After the aging treatment, water quenching is performed at a water temperature of 20-30 °C and a transfer time of no more than 10 s. After water quenching, re-aging treatment is performed at a re-aging temperature of 110-130 °C and a holding time of 20-25 h. After the re-aging treatment, the sample is air-cooled to room temperature.
Citation Information
Patent Citations
Method for preparing Al-Mg-based high-strength aluminum alloy through selective laser melting
CN112981157A
5-series aluminum alloy
CN113817937A
Corrosion-resistant Al-Mg-Mn-Sc series aluminum alloy and preparation method thereof
CN115505800A
Cited By
Additive manufacturing Al-Cu-Sc alloy and high-toughness preparation method thereof
CN121472663A
Nickel-based superalloy for additive manufacturing and preparation method of nickel-based superalloy
CN122099304A
A nickel-based superalloy for additive manufacturing and its preparation method
CN122099304B
A laser powder bed fusion prepared zrb2 modified crack resistant aluminum alloy and a preparation method thereof
CN122769469A